Representation of Authoritarian Power in Naguib Mahfouz's Novel "Al Karnak": A Sociological Study of Literature - Zahra, Nasywa Athirah Nathania; Putri, Aulia Zahra Maulidya (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Naguib Mahfouz is one of Egypt’s most important writers, having won the Nobel Prize in Literature in 1988. His works frequently address social and moral issues, as well as the dynamics of Egyptian society undergoing cultural and political change. One work that represents these conditions is the novel *Al-Karnak*, which depicts the post-revolutionary socio-political situation in Egypt, characterized by the dominance of state power and the strong role of security forces. Through the characters and events presented, this novel illustrates how political power operates repressively through practices of arrest, interrogation, and torture of citizens. These conditions simultaneously reflect a critique of the authoritarian political system and depict how the abuse of power can destroy the lives and ideals of the younger generation, while creating a social climate filled with fear within society. This study aims to analyze the representation of political power in the novel Al-Karnak through a literary sociology approach. The method used in this study is a qualitative method employing descriptive-interpretive analysis of the novel’s text. The analysis employs Michel Foucault’s concept of power to examine how power practices are represented in the relationship between the state, security apparatus, and society. The findings reveal that political power in the novel *Al-Karnak* is portrayed as repressive and dominant, exercised through mechanisms of surveillance, arrest, and torture against individuals deemed suspicious by the state. These practices of power not only restrict individual freedom but also shatter the idealism of the younger generation, who previously held hopes for social change. Furthermore, repressive power contributes to creating social conditions marked by fear, distrust, and social trauma. Thus, the novel *Al-Karnak* can be understood as a social critique of authoritarian political power practices in society.